Serum Estrogen Concentration in Relation to Estrous Duration of Thin-tail Ewes with Inducted of PMSG - Sugiyatno, Sugiyatno; Sumaryadi, MS; Haryati, Haryati (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2001)
Fifteen thin tail ewes were used in to study of contribution of maternal serum estrogen concentration this in relation to estrous duration with inducted of PMSG. The first step, all experiment ewes were injected prostaglandin (7.5 mg luprositol per head) i.m. as much twice of interval day 11 to homogeneity follicle growth phase. In the estrous observed was estrous (700 IU duration, then blood sampling taken out of vena jugulars to analyses of estrogen. The second step, all experiment ewes were inducted PMSG (700 IU per head), then in the estrous observed was same as the first step. The result of experiment show that induction of PMSG influence to maternal serum estrogen concentration has different significantly (P<0.01)and estrous duration has different significant (P<0.05).Maternal serum estrogen concentration prior and post of induction of PMSG contributed 25.28 and 57.12 percent, respectively. It was concluded that the estrous duration in relation to increased maternal serum estrogen concentration. (Animal Production 3(1): 40-44 (2001) Key Words: Estrogen, estrous, ewes